THE EFFECT OF PROFITABILITY MEDIATION ON INCREASING COMPANY VALUE THROUGH CORPORATE SOCIAL RESPONSIBILITY - Mahdi Mahdi; Irwan Moridu; Teguh Setiawan Wibowo; Andrew Shandy Utama; Iwan Adinugroho; Amalia Amalia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research is motivated by the importance of corporate value as an indicator of prosperity for shareholders. This study aims to identify and analyze the effect of mediating profitability on increasing firm value through corporate social responsibility. The population of this study are all manufacturing companies listed on the IDX for 2019-2021. Using the purposive sampling technique, a sample of 15 companies was obtained. The measurement of the profitability variable uses an indicator from Hartono (2018), namely Return on Equity (ROE). The measurement of corporate social responsibility variables uses seven indicators from Sembiring (2005), namely environment, energy, occupational health and safety, workforce, products, community involvement, and the general public. The measurement of firm value variables uses indicators from Weston and Copeland (2008), namely the Price Earning Ratio (PER). The collected data were then analyzed using descriptive statistics, inferential statistics, and regression analysis. The results of this study indicate that 1) Corporate Social Responsibility has a positive and significant effect on firm value, and 2) Profitability is able to mediate the effect of Corporate Social Responsibility on firm value. The results of this research indicate that if the company wants to increase the value of the company, the company must increase Corporate Social Responsibility and be strengthened by Profitability.